Posaconazole after previous antifungal therapy with voriconazole for therapy of invasive aspergillus disease, a retrospective analysis - Heinz, Werner J.; Egerer, Gerlinde (Mycoses, 2013)
Invasive aspergillosis is an important cause of morbidity and mortality in haematological patients. Current guidelines recommend voriconazole as first-line therapy. A change in class of antifungal agent is generally recommended for salvage therapy. The focus of this analysis was to assess if posaconazole is suitable for salvage therapy following voriconazole treatment. This was a retrospective investigation on patients with sequential antifungal therapy of posaconazole after voriconazole identified at four German hospitals. Response rates at 30 and 60 days following start of posaconazole application and toxicity of azoles by comparing liver enzymes and cholestasis parameters were evaluated. Data were analysed by descriptive statistics. Overall, the success rate was 72.2% [15 of 36 patients showed complete response (41.7%), 11 patients partial response (30.6%) at any time point], eight patients failed treatment and two were not evaluable. Mean laboratory values increased during voriconazole and decreased during posaconazole treatment: aspartate aminotransferase (increase: 31.9 U l−1 vs. decrease: 19.6 U l−1), alanine aminotransferase (32.4 U l−1 vs. 19.8 U l−1), gamma-glutamyl transferase (124.2 U l−1 vs. 152.3 U l−1) and alkaline phosphatase (71.5 U l−1 vs. 40.3 U l−1) respectively. No patient discontinued posaconazole therapy due to an adverse event. In this analysis posaconazole was a safe and effective antifungal salvage therapy in patients with prior administration of another triazole.
Published online 21 November 2012
Gesehen am 20.04.2018